Frequency of In-Stent Restenosis (ISR) in Diabetic Patients Following Percutaneous Coronary Intervention (PCI) for Stable Coronary Artery Disease (CAD) with Angina Pectoris - Ibrahim Shah, Umar Ibrahim Paracha, Saif Ullah, Samiullah Khan, Matiullah Khan, Akhtar Sher (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In-stent restenosis (ISR) remains a significant concern following percutaneous coronary intervention (PCI), particularly among diabetic patients who are at higher risk due to underlying vascular and metabolic factors. This research sought to establish the prevalence of ISR among diabetic patients with stable coronary artery disease and assess the relevant clinical and operative variables. Methods: A cross-sectional analytical study was conducted at Gajju Khan Medical College/Bacha Khan Medical Complex Swabi and Pak Welfare Cardiac Cath Lab, Peshawar, from February 2022 to January 2023. A total of 110 diabetic patients who underwent PCI for stable CAD and returned for follow-up coronary angiography were included. Clinical profiles, angiographic characteristics, and stent details were reviewed. ISR was defined as ≥50% narrowing within or near the stented segment. Statistical analysis was performed to identify associations between ISR and various risk factors. Results: ISR was detected in 25.4% of patients. Factors significantly associated with ISR included poor glycemic control (HbA1c ≥7%), longer duration of diabetes, dyslipidemia, triple vessel disease, long lesions, small vessel diameter, and use of longer or smaller stents. Symptom recurrence and the need for repeat revascularization were remarkably more prevalent among patients diagnosed with ISR. Conclusion: Diabetic patients remain at high risk for ISR despite the use of modern stent technologies. Recognizing clinical and angiographic predictors can help guide preventive strategies and improve patient outcomes following PCI. Keywords: ‘In-stent restenosis, diabetes mellitus, percutaneous coronary intervention, coronary artery disease, drug-eluting stents, angioplasty, risk factors’